Соціально-економічний розвиток слобожанських монастирів середини XVII – XVIIIст. Монастирське землеволодіння - Кравченко, О. (Сiверянський лiтопис, 2010)
Стаття присвячена історії розвитку монастирського замлеволодіння на території Сумського та Охтирського полків у середині XVII – XVIII ст. Статья посвящена истории развития монастырского земелевладения на территории Сумского и Ахтырского полков в середине XVII – XVIII вв. Основой экономического развития монастырей становится землевладение. Приобретение и жертвование монастырям земельных участков стало толчком к обогащению и развитию монастырских хозяйств. В середине XVIII в. монастыри превращаются из небольших хозяйств в крупных землевладельцев. The article is devoted history of development of the monasterial's landed domain on territory of Sumskуi and the Ahtyrskyi regiments in the middle of XVIIth. – XVIIIth. c. To become the basis of economic development of monasteries landed domains. The acquisition and the donation monasteries of lot lands became a shove to enrichment and development of monasterial's economy. In the middle of XVIIIth. cent. monasteries transform from the small economies in large landed domains.